GeoAI in the US Geological Survey for topographic mapping. Issue 1 (30th August 2021) - Usery, E. Lynn; Arundel, Samantha T.; Shavers, Ethan; Stanislawski, Lawrence; Thiem, Philip; Varanka, Dalia
Abstract: Geospatial artificial intelligence (GeoAI) can be defined broadly as the application of artificial intelligence methods and techniques to geospatial data, processes, models, and applications. The application of these methods to topographic data and phenomena is a focus of research in the US Geological Survey (USGS). Specifically, the USGS has researched and developed applications in terrain feature extraction, hydrographic network extraction, and semantic modeling. This article is a documentation of the recent work and current state of research and development. The article helps define the accomplishments and directions of research and applications in fields of GeoAI for topographic mapping within the USGS and more broadly.